Three-dimensional electrical structure in the northwestern sector of the Sichuan-Yunnan diamond block - Zhang, Yunyun; Chen, Xiaobin; Wang, Peijie; Cai, Juntao; Liu, Zhongyin; Zhang, Jiong; Huang, Xingxing (Frontiers in Earth Science, 2025)
The Sichuan-Yunnan diamond block is a significant region of material flow from the Tibetan Plateau. However, its northwest electrical boundary remains undefined. Our study conducted a magnetotelluric profile from Chazha to Luomai across the geological boundary of the Sichuan-Yunnan block in its northwest sector. Using the nonlinear conjugate gradient three-dimensional inversion method, we obtained the deep electrical structure across the northern part of the block. Our findings reveal distinct segmental characteristics in the electrical structure along the profile. Marked by a high-resistivity zone along the Dedeng-Batang-Riyu fault, two high-conductivity layers exist in the upper-middle crust of the southwestern and central sections of the profile, at depths of 5–20 km and 10–30 km, respectively. Thus, our study suggests that the northwest boundary of the Sichuan-Yunnan diamond block, contrary to previous studies that considered it a transitional boundary, is located at the Dedeng-Batang-Riyu fault. Here, the boundary is a high-resistivity barrier, electrically isolating the Qiangtang block in the southwest from the Sichuan-Yunnan block in the northeast. The two significant high-conductivity zones in the upper-middle crust appear within the block’s interior, contrasting with previous assumptions of lower crustal flow.